Blockchain-Based DNS Root Zone Management Decentralization for Internet of Things. (8th February 2021) - Zhang, Yu; Liu, Wenfeng; Xia, Zhongda; Wang, Zhongze; Liu, Lu; Zhang, Weizhe; Zhang, Hongli; Fang, Binxing
Abstract : Domain Name System (DNS) is a widely used infrastructure for remote control and batch management of IoT devices. As a critical Internet infrastructure, DNS is structured as a tree-like hierarchy with single root zone authority at the top, which puts the operation of DNS at risk from single point of failure. The current root zone management is lack of transparency and accountability, since only the root zone file is published as the final outcome of operations inside the root zone authority. Towards distributed root zone operation in DNS, this paper presents a blockchain-based root operation architecture—RootChain, composed of multiple root servers. On the basis of maintaining the single root authority for top-level domain (TLD), RootChain decentralizes TLD data publication by empowering delegated TLD authorities to publish authenticated data directly. The transparency and accountability of root zone operation are attained by smart-contracting the whole life cycle of TLD operation and logging all operations on the chain. RootChain is transparent to recursive/stub resolver and DNS/DNSSEC-compatible. A proof-of-concept prototype of RootChain has been implemented with Hyperledger Fabric and evaluated by experiments.